Sustained activation of non-canonical NF-κB signalling drives glycolytic reprogramming in doxorubicin-resistant DLBCL - Lim, Shen Kiat (2023)
DLBCL is the most common lymphoma with high tumor heterogeneity. Treatment refractoriness and relapse from R-CHOP therapy in patients remain a clinical problem. Activation of the non-canonical NF-κB pathway is associated with R-CHOP resistance. However, downstream targets of non-canonical NF-κB mediating R-CHOP-induced resistance remains uncharacterized. Here, we identify the common mechanisms underlying both intrinsic and acquired resistance that are induced by doxorubicin, the main cytotoxic component of R-CHOP. We performed global transcriptomic analysis of (1) a panel of resistant versus sensitive and (2) isogenic acquired doxorubicin-resistant DLBCL cell lines following short and chronic exposure to doxorubicin respectively. Doxorubicin-induced stress in resistant cells activates a distinct transcriptional signature that is enriched in metabolic reprogramming and oncogenic signalling. Selective and sustained activation of non-canonical NF-κB signalling in these resistant cells exacerbated their survival by augmenting glycolysis. In response to doxorubicin, p52-RelB complexes transcriptionally activated multiple glycolytic regulators with prognostic significance through increased recruitment at their gene promoters. Targeting p52-RelB and their targets in resistant cells increased doxorubicin sensitivity in vitro and in vivo. Collectively, our study uncovered novel molecular drivers of doxorubicin-induced resistance that are regulated by non-canonical NF-κB pathway. We reveal new avenues of therapeutic targeting for R-CHOP-treated refractory/relapsed DLBCL patients.